IMUNITAS ALAMIAH: EOSINOPHIL EXTRACELLULAR TRAPS (EET) - Safari Wahyu Jatmiko (Biomedika, 2013)
Eosinophils play a role in the defense against viruses, bacteria, fungi and parasites, as well as be involved in the pathogenesis of allergic and autoimmune diseases. The role of eosinophils in the defense against bacterial run by enzymes found in the granules such as MBP, ECP, EPO, and EDN, and spending EET. EET formation is determined by the presence of free radicals and intracellular calcium. The antimicrobial function of EET played by Histon.Keywords: eosinophil , Eosinophils extracellular traps